Red light emission of Mn doped beta-tricalcium phosphate -Ca3(PO4)2 - Van, Hoang Nhu; Hoan, Bui Thi; Duy-Hung, Nguyen; Tam, Phuong Dinh; Khoi, Nguyen Thi; Thang, Cao Xuan; Vuong-Hung, Pham` (Vietnam Journal of Chemistry, 2017)
This paper is the first report on the red light emission of manganese (Mn) doped beta-tricalcium phosphate (b-Ca3(PO4)2, TCP) synthesis by co-precipitation method followed by thermal annealing. The annealed Mn doped TCP phosphor showed dominant spheres with a diameter of about 500 nm. The influences of the Mn concentration, annealing temperature, and atmospheres on the photoluminescence intensities of the phosphors were investigated and the results indicate that the annealing temperatures and Mn concentrations are the main factors. The phosphor showed visible emission peaks appeared at about 660 nm and 580 nm results in from the 4T1-6A1 transitions within Mn2+ ion. The Mn-TCP phosphor may serve as a candidate for light-emitting diode application in agriculture lighting. Keywords. Hydroxyapatite; manganese; luminescence; tricalcium phosphate.